2018
DOI: 10.15171/mejdd.2018.114
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Cytomegalovirus Colitis in Inflammatory Bowel Disease with Different Regimes of Ganciclovir

Abstract: BACKGROUND Cytomegalovirus (CMV) infection is common in individuals with inflammatory bowel disease (IBD) and is responsible for relapse, increased severity, and poor outcome if left untreated. Ganciclovir is the mainstay of treatment but data regarding its use, mode of administration, and duration of treatment is poorly described. We reviewed the practice of treating CMV colitis with different regimes of ganciclovir at a district NHS hospital to compare the clinical outcome. METHODS 35 patients with IBD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
(37 reference statements)
0
5
0
2
Order By: Relevance
“…This success has been confirmed in other case reports or analysis of limited cohorts of patients ( Table 3 ). The duration of antiviral treatment should be at least of two weeks and, if possible, by intravenous route [ 157 ], as the inflammation of the gut may compromise the drug absorption. For the management of such patients, we proposed an algorithm that considers the CMV viral load in inflammatory tissue ( Figure 3 ).…”
Section: Active Pejorative Role Of CMV Reactivations In Uc Flare-umentioning
confidence: 99%
“…This success has been confirmed in other case reports or analysis of limited cohorts of patients ( Table 3 ). The duration of antiviral treatment should be at least of two weeks and, if possible, by intravenous route [ 157 ], as the inflammation of the gut may compromise the drug absorption. For the management of such patients, we proposed an algorithm that considers the CMV viral load in inflammatory tissue ( Figure 3 ).…”
Section: Active Pejorative Role Of CMV Reactivations In Uc Flare-umentioning
confidence: 99%
“…15 The potential negative impact of CMV on IBD warrants the requests for CMV IHC testing in biopsies. 15,16 However, the prevalence of CMV reactivation/ infection in patients with IBD is still uncertain, since prior studies have evaluated only selected patients or used different methods to diagnose CMV infection. 17 Previous research has suggested a range of 4% to 16% for CMV infection rate in patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a small retrospective study in patients with IBD and CMV colitis, a 2-week treatment with oral valganciclovir was associated with more colectomies and decreased clinical response than 2-week intravenous ganciclovir [63].…”
Section: Management Antiviral Therapymentioning
confidence: 91%